EFL LEARNERS' PARTICIPATION AMONG PROFICIENCY LEVELS: INSIGHTS FROM STUDENTS AND TEACHERS - Risna Asita Sari; Nukmatus Syahria; Jessica Ong Hai Liaw (Indonesian EFL Journal, 2026)
While prior research establishes that participation is affected by proficiency, instruction, motivation, and anxiety, few studies investigate participation by integrating observable classroom behavior with teachers' interpretations, particularly within Indonesian university EFL contexts. To bridge this disparity, this study aimed to describe how students with varying English proficiency levels participate in an English Intensive Program at an Islamic university in Surabaya, Indonesia, and to explore how teachers interpret students’ participation in light of those proficiency levels. Data were collected through non-participant classroom observations and in-depth interviews with university students from two classes and five teachers, and were analysed using thematic analysis. The study found that students’ participation appeared in many forms and was not limited to speaking. Higher- and intermediate-proficiency students tended to participate verbally, mostly when prompted by the teacher. Meanwhile, lower-proficiency students participated by listening, taking notes, following instructions, and completing tasks. Teachers interpreted participation by considering students’ proficiency level, confidence, task difficulty, and classroom situation. Silence was often viewed as limited language ability or low confidence rather than a lack of interest. The study contributes to a deeper understanding of classroom involvement in EFL environments. The results support the notion that participation is dependent upon context and socially created, rather than just verbal. It also shows that observed stillness can indicate cognitive engagement rather than disengagement. By combining teachers' perspectives with observed students' behaviours, this study suggests that participation should be investigated through both behavioural and interpretive lenses. Future research should explore classroom participation and consider linguistic, nonverbal, affective, and contextual elements.